2011
DOI: 10.1089/fpd.2009.0461
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the Prevalence of EnteropathogenicYersiniain Slaughter Pigs from Belgium, Italy, and Spain

Abstract: Tonsils of 829 fattening pigs originating from Belgium (n ¼ 201), Italy (n ¼ 428), and Spain (n ¼ 200) were collected between 2005 and 2007 to study the prevalence of enteropathogenic Yersinia in slaughter pigs. Isolation of Yersinia enterocolitica and Yersinia pseudotuberculosis was done by selective enrichment and by cold enrichment for 7 and 14 days. Pathogenic Y. enterocolitica and Y. pseudotuberculosis isolates were identified by polymerase chain reaction targeting the chromosomal genes ail and inv, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 42 publications
4
40
1
Order By: Relevance
“…pseudotuberculosis strains were only isolated from wild boars in Switzerland. However, it has recently been shown that Y. pseudotuberculosis can also be found in domestic pigs but that the prevalence is clearly lower than the prevalence of Y. enterocolitica (Martínez et al, 2009(Martínez et al, , 2010a(Martínez et al, , 2010b. Further studies are needed to show that wild boars are a more important reservoir for Y. pseudotuberculosis than domestic pigs.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…pseudotuberculosis strains were only isolated from wild boars in Switzerland. However, it has recently been shown that Y. pseudotuberculosis can also be found in domestic pigs but that the prevalence is clearly lower than the prevalence of Y. enterocolitica (Martínez et al, 2009(Martínez et al, , 2010a(Martínez et al, , 2010b. Further studies are needed to show that wild boars are a more important reservoir for Y. pseudotuberculosis than domestic pigs.…”
Section: Resultsmentioning
confidence: 98%
“…Bioserotype 4=O:3 is widely distributed and the most common type causing human yersiniosis in Europe (EFSA, 2009). It is also the most common type in European pig population (Martínez et al, 2009(Martínez et al, , 2010a(Martínez et al, , 2010b. Bioserotype 2=O:9 is the second most common type identified in human yersiniosis in Europe followed by bioserotype 2=O:5,27.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations